Farmer Perspectives on Sustainable Urban Farming Tourism: A Case Study of Bali's Subak Lestari Program - Ni Wayan Purnami Rusadi; I Gde Pitana; I Nyoman Sunarta; I Nyoman Sukma Arida (Pusat Kajian Bali Universitas Udayana, 2024)
Bali's economic landscape, intricately interwoven with tourism, integrates cultural-urban agriculture via the Subak system. Subak is an organization owned by the farmers in Bali that specifically regulates water management. The government has selected several Subak in urban area to become dynamic agricultural centers named Subak Lestari. The research explores farmer perspectives on urban agriculture tourism and offering insights for future sustainable urban agriculture and cultural tourism. This qualitative study is involving 23 farmers of Subak Lestari management and reflecting scores in technical (4.01), socio-cultural (3.87), economic (4.29), and environmental (4.32) aspects. These assessments underscore confidence in Subak Lestari's potential to catalyze a development in tourism-centric urban agriculture. Farmers seriously support positions of Subak Lestari as a potent force in reshaping urban agriculture. The study advocates for stakeholders to foster a sustainable fusion of traditional agriculture and tourism to safeguard agricultural spaces and ensuring urban farmers existence.